Buddhabhāsā ta rāʺ toʻ, ʼa khre kham ʼa chaṅʻ (Sāsanā reʺ Vanʻ krīʺ Thāna, Sāsanā reʺ Ūʺ cīʺ Thāna Pum nhipʻ Tuikʻ, 1994)
Introduction to Buddhist doctrines; includes instructions on conduct of life for Burmese Buddhist youth.